Melatonin supplementation for severe and intractable sleep disturbance in young people with genetically determined developmental disabilities: short review and commentary. Issue 11 (19th November 2003) - Turk, J
Abstract : Serious childhood developmental disabilities are common, and are debilitating for the individual and their family. Increasingly these are being shown to have genetic bases. Associated challenging behaviours are frequent, one of the commonest being severe and intractable sleep disturbance. This is associated with daytime behaviour problems, poor developmental and academic progress, and substantial familial psychopathology. Social and behavioural approaches ("sleep hygiene" measures) have, to an extent, revolutionised management; however, many individuals remain unresponsive. Modern medications therefore play increasingly important complementary roles in conjunction with psychological, educational, and social strategies. This paper reviews evidence for the frequency and severity of sleep disturbance in children and young people with severe intractable neurodevelopmental disabilities. The potential benefits of judicious and carefully monitored use of medication are described, with a focus on the importance of melatonin as a sleep inducer. It is concluded that melatonin is a potentially useful and safe adjunct to psychological and social approaches for severe sleep disturbance in this client group.